Leucocyte integrin and CR1 expression on peripheral blood leucocytes of patients with rheumatoid arthritis. Issue 3 (March 1992) - McCarthy, D; Taylor, M J; Bernhagen, J; Perry, J D; Hamblin, A S
Abstract : Expression of the leucocyte integrins (CD11a, b, c/CD18) and of CD35 (CR1) on leucocytes from the peripheral blood of patients with rheumatoid arthritis (RA) (n = 14) and control subjects (n = 12) was measured by flow cytometry using a rapid fixation and leucocyte preparation procedure. The mean (SE) percentages of lymphocytes expressing CD11a (RA 93.4 (1.7)%; controls 97.2 (1.8)%) and CD18 (RA 91.3 (2.3)%; controls 97.0 (2.6)%) were lower and the percentage of monocytes expressing CD11b (RA 86.9 (11.4)%; controls 78.4 (11.9)%) and CR1 (RA 62.6 (15.5)%; controls 36.6 (17.6)%) were higher in patients with RA than in controls. In addition, the mean fluorescence intensity of CD18 (RA 22.1 (2.3); controls 30.7 (2.5)) on lymphocytes was decreased and that of CD11b (RA 4.5 (0.8); controls 2.9 (0.9)) and CR1 (RA 2.4 (0.4); controls 1.5 (0.5)) on monocytes was increased in patients with RA compared with controls. The functional importance (if any) of the altered expression of the antigens on lymphocytes is not yet known. Altered expression on monocytes is consistent with activation within the circulation.